2012
DOI: 10.1371/journal.pone.0031601
|View full text |Cite
|
Sign up to set email alerts
|

XIAP Is a Predictor of Cisplatin-Based Chemotherapy Response and Prognosis for Patients with Advanced Head and Neck Cancer

Abstract: BackgroundApproximately 60–80% of patients with advanced head and neck squamous cell carcinoma (HNSCC) die within five years after diagnosis. Cisplatin-based chemotherapy is the most commonly used palliative treatment for these patients. To evaluate the prognostic value of X-linked inhibitor of apoptosis (XIAP) level as a potential biomarker in these patients, we investigated the relationship between XIAP expression and cisplatin response of these patients and their prognosis.Methodology/Principal FindingsSixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 25 publications
1
51
0
1
Order By: Relevance
“…XIAP overexpression is important in CDDP resistance in advanced HNC. 22,23 Although our study indicates that XIAP interacts with GSN and that the extent of this interaction and the intracellular trafficking of the complex is differentially regulated by CDDP in chemosensitive and chemoresistant HNC cells, the physiological significance of these findings remains to be determined. However, this finding suggests that GSN acts as a mobile dock for the signaling pathway.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…XIAP overexpression is important in CDDP resistance in advanced HNC. 22,23 Although our study indicates that XIAP interacts with GSN and that the extent of this interaction and the intracellular trafficking of the complex is differentially regulated by CDDP in chemosensitive and chemoresistant HNC cells, the physiological significance of these findings remains to be determined. However, this finding suggests that GSN acts as a mobile dock for the signaling pathway.…”
Section: Discussionmentioning
confidence: 76%
“…2 XIAP is also important for regulating CDDP sensitivity in head-and-neck cancer (HNC) cells. 9,22,23 In our study, we aimed to define the role of GSN in chemoresistance in HNC, to examine the underlying molecular mechanism involved and to evaluate the possibility of using GSN as a therapeutic target.…”
mentioning
confidence: 99%
“…Despite extensive efforts, few improvements in treatment have been made in the last 30 years, and the molecular basis of acquired chemoresistance in HNSCC remains largely unknown and continues to be a major complication for chemotherapy (5,6). Clearly, there is an urgent need for understanding mechanisms of therapy resistance and developing more effective novel chemotherapeutic treatment options to improve the survival of HNSCC patients.…”
mentioning
confidence: 99%
“…It plays a critical role in the inhibition of apoptosis in both death receptor-mediated and mitochondria-mediated pathways [23], [24]. A recent study further demonstrated that XIAP is a predictor of chemotherapy response and prognosis for advanced head and neck cancer patients [25]. Therefore, we also examine the effect of NSC745885 on the XIAP gene and protein expression in oral cancer cells, we treated the SAS cancer cells with different concentrations (0 µM, 0.5 µM, 1.0 µM, 1.5 µM, and 2.0 µM) for 24 hours, and then determined their change in gene expression by using the Q-PCR.…”
Section: Resultsmentioning
confidence: 98%